Turnpike Property for Two-Dimensional Navier–Stokes Equations - Zamorano-Aliaga, S (Birkhauser Verlag AG, 2018)
In this paper we study the turnpike phenomenon arising in the optimal distributed control tracking-type problem for the Navier–Stokes equations. We obtain a positive answer to this property in the case when the control is time-dependent function and also when it is independent of time. In both cases we prove an exponential turnpike property assuming that the stationary optimal state satisfies certain properties of smallness. © 2018, Springer International Publishing AG, part of Springer Nature.
Keywords: Navier-Stokes equations; Optimal control problems; Turnpike property; Asymptotic stability; Oseen equation